Experience marketing through authenticity and escapism: Drivers of revisit intention in Sumatra’s natural heritage tourism - Lestari, Indawati; Suryani, Wan (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study aims to analyze the influence of destination attributes, escapism, and authenticity on place attachment and memorable tourism experience, and to examine the mediating role of place attachment on revisit intention. This study was conducted on tourists visiting leading destinations in Sumatra Province, such as the Toba Caldera Geopark and the Tropical Rainforest Heritage of Sumatra. Data were collected through a survey of 300 respondents chosen by purposive sampling and analyzed using a quantitative approach with partial least squares-structural equation modeling (PLS-SEM) through SmartPLS 3.0. The results show that destination attributes, escapism, and authenticity have a positive and significant effect on place attachment and memorable tourism experience. In addition, place attachment is proven to mediate the relationship between these three variables and revisit intention. These findings confirm that tourists’ emotional attachment to a destination plays a significant role in driving revisit intention. Theoretically, this study broadens the understanding of the relationship between tourist psychological factors and post-tourism behavior in the context of nature and cultural tourism in Indonesia. Practically, the results of this study provide implications for destination managers to strengthen the elements of authenticity, experience quality, and emotional value of destinations to build sustainable tourism.